A systemic review of Toxic Death in clinical oncology trials: an Achilles’ heel in safety reporting revisited - Penninckx, B; Van de Voorde, W M; Casado, A; Reed, N; Moulin, C; Karrasch, M (British journal of cancer, 2012)
Background: Toxic death is defined as study treatment-related mortality and as such is considered as an iatrogenic death. This belongs to unnatural death where an autopsy is advised. Until now, conventional autopsy is the gold standard to discriminate between pre- and post-mortem discrepancies. Methods: The consequences of lack of systematically performing an autopsy will be explored in the setting of oncological clinical trials. Results: During more than one decade, 6428 Serious Adverse Events have been registered in the EORTC Safety database on a total of 34 734 subjects. The number of deaths were 764 (mortality rate of 2.2%) whereof 255 (rate of 0.7%) toxic deaths. In 89.8% of these toxic deaths, no autopsy has been done; in 25.1% (64 cases) an inconsistent cause of death was found based on studying of the medical narrative. The autopsy rate was only 10.2% (26 out of 255) and, in 46.2% of the performed autopsies, there was a clinical pathological discrepancy. conclusion: When no autopsy is performed, there is a high risk for a wrong diagnosis in case of suspected toxic death. The high discrepancy rate, possibly due to a low autopsy rate, shows that toxic death is an Achilles’ heel in iatrogenic mortality.